Ethernet-ZigBee gateway - Almeida, Nuno José Coelho (2013)
Telecommunications have been present in our daily lives for a long time. The emergence of the Internet has revolutionized the way of communicating, allowing the establishment of a global scale network. The state of the Internet has been evolving from the "Internet of people" to become the "Internet of things" or the "Internet of everything". The huge increase of "smart" devices, i.e. with processing and communication capabilities, memory and the ability of gathering information, has been the main cause of this paradigm shift. The referred devices communicate according to the Machine-to-Machine concept, which allows an end-to-end communication between them, without (or with limited) human intervention. Home automation has been growing and it uses the described concepts; it allows the use of devices in order to automatize home-related tasks. A usual scenario allows the control of both lighting, temperature and sound systems through a central device that can be connected to the Internet, allowing the remote access and control of the entire system. The gateway is the device that allows a connection with other networks (e.g. Internet). The present document proposes an implementation of an Ethernet- ZigBee gateway that enables the remote monitoring and control of an HVAC (Heating, Ventilation and Air Conditioning) system through the Web browser.